2020
DOI: 10.1021/acsanm.0c01471
|View full text |Cite
|
Sign up to set email alerts
|

Gallium-Doped Zinc Oxide Nanoparticle Thin Films as Transparent Electrode Materials with High Conductivity

Abstract: Gallium-doped zinc oxide (GZO) nanoparticles (NPs) have been synthesized by a solvothermal synthesis method using gallium chloride and zinc chloride as precursors in anhydrous methanol along with bases. Systematic investigations have revealed that H2O, formed through the condensation of metal hydroxides to obtain GZO NPs, not only enhances the production of layered compounds as byproducts but also accelerates Ostwald ripening to reduce the amount of doped gallium ions. To overcome H2O generation during NP grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 73 publications
0
18
0
Order By: Relevance
“…Unless otherwise noted, all the characterization tests were performed under atmospheric conditions based on our previous studies. [5,37,41] The average temperature was 28 °C. The crystallographic structures of the ITO powders were identi ed by a Rigaku Ultima-IV XRD measurement system using a Cu Kα radiation source (40 kV, 40 mA) equipped with a D/teX Ultra detector.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Unless otherwise noted, all the characterization tests were performed under atmospheric conditions based on our previous studies. [5,37,41] The average temperature was 28 °C. The crystallographic structures of the ITO powders were identi ed by a Rigaku Ultima-IV XRD measurement system using a Cu Kα radiation source (40 kV, 40 mA) equipped with a D/teX Ultra detector.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, we demonstrated the preparation of galliumdoped zinc oxide (GZO) on glass substrates as TCO thin lms by the GZO NP-mist deposition method. [37] Here, GZO NPs controlled in mean particle size were originally synthesized by a solvothermal method using a mixture of NaOH/NaOMe as bases. [37] The transparency, haze, and resistivity of the GZO NP-mistdeposited thin lms on glass substrates were more than 99% at 600 nm, 0.3%, and 5 x 10 -2 Ω•cm after annealing at 300 °C, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Watanabe 35 and Kim 36 et al reported the preparation of porous TiO 2 films from preheated and dried spray mists, respectively. More recently, we demonstrated the preparation of gallium-doped zinc oxide (GZO) on glass substrates as TCO thin films by the GZO NP-mist deposition method 37 . Here, GZO NPs controlled in mean particle size were originally synthesized by a solvothermal method using a mixture of NaOH/NaOMe as bases 37 .…”
Section: Introductionmentioning
confidence: 99%
“…More recently, we demonstrated the preparation of gallium-doped zinc oxide (GZO) on glass substrates as TCO thin films by the GZO NP-mist deposition method 37 . Here, GZO NPs controlled in mean particle size were originally synthesized by a solvothermal method using a mixture of NaOH/NaOMe as bases 37 . The transparency, haze, and resistivity of the GZO NP-mist-deposited thin films on glass substrates were more than 99% at 600 nm, 0.3%, and 5 × 10 −2 Ω cm after annealing at 300 °C, respectively.…”
Section: Introductionmentioning
confidence: 99%